Effects of pre-CABG program on discharge readiness and surgery outcomes for patients undergoing elective CABG surgery: a study protocol for a randomised control trial - Seyed Mohammad Riahi; Ali Khanipour-Kencha; Masoumeh Zakerimoghadam; Pouya Dolat Abadi; Zahra Abbasi Dolat Abadi; Mehrzad Rahmanian (BMJ Open)
Introduction Cardiovascular diseases, a leading cause of death globally, impose significant health and economic burdens, particularly in countries like Iran. Coronary artery bypass grafting (CABG) is a common intervention for ischaemic heart disease, yet it entails a long recovery process with potential complications and psychological impacts. This study aims to evaluate the effectiveness of a prehabilitation programme (pre-CABG) on postoperative outcomes and discharge readiness in patients undergoing elective CABG.Methods and analysis This randomised controlled trial involves 60 patients diagnosed with coronary artery disease at Imam Khomeini Hospital Complex, Tehran. Participants will be randomly assigned to either the intervention group, receiving the pre-CABG programme, or the control group, receiving standard care. The pre-CABG programme includes patient education, stress management techniques, respiratory muscle training and nutritional guidance. Primary outcomes include discharge readiness, duration of intubation, Intensive Care Uniy (ICU) stay, occurrence of atelectasis, onset of mobility, hospital stay and levels of anxiety and depression. Secondary outcomes include the rate of 30-day readmissions. Data collection will involve standardised scales and checklists administered at various stages preoperation and postoperation.Ethics and dissemination The research study has received approval from the Research Ethics Committee at Tehran University of Medical Sciences’ School of Nursing and Midwifery and Rehabilitation. All participants must provide written consent for their involvement in this study. The findings will be shared with appropriate groups and published in peer-reviewed journals.Trial registration number The study is registered with the Iranian Registry of Clinical Trials under the ID IRCT20231019059768N1.